EVALUATION OF IMAGE QUALITY AND LESION CONSPICUITY IN HEPATIC IMAGING USING TRIPLE-PHASE MULTI-DETECTOR COMPUTED TOMOGRAPHY - PRATAP, BHANU; MEENA, BIJENDAR KUMAR; YADAV, RAJESH; KUMAR, GOURAV; TRIPATHI, HIMANSHU (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Aim: To evaluate image quality and lesion conspicuity of hepatic lesions using triple-phase Multi-Detector Computed Tomography (MDCT) and determine the diagnostic value of each phase Methods: A cross-sectional observational study was conducted on 135 patients undergoing triple-phase MDCT for suspected hepatic lesions. Arterial, portal venous and delayed phases were acquired using a Siemens 128-slice MDCT scanner. Lesion conspicuity was graded on a 5-point scale by two experienced radiologists. Statistical analysis included descriptive measures, Chi-square test, and Friedman test to compare conspicuity across phases. Results: Portal venous phase showed the highest conspicuity, with nearly 50% of lesions scoring 4–5, indicating good to excellent visibility. Arterial phase demonstrated moderate conspicuity, especially in hypervascular lesions, while the delayed phase highlighted washout patterns characteristic of malignant lesions. Although statistical differences between phases were not significant (p > 0.05), descriptive analysis showed clinically meaningful variation, with the portal venous phase offering the best lesion–liver contrast. Conclusion: Triple-phase MDCT provides comprehensive evaluation of hepatic lesions. The portal venous phase yields maximum conspicuity, while arterial and delayed phases offer essential complementary information, improving overall diagnostic confidence.